An unusual thrombus location in a Heartmate 3TM device with fatal outcome. (July 2020) - Banfi, Carlo; Rigamonti, Fabio; Ahmadov, Kamran; Meyer, Philippe; Hachulla, Anne-Lise; Craviari, Cecilia; Fontana, Pierre; Bendjelid, Karim; Giraud, Raphaël
Even if the HeartMate 3 TM left ventricular assist device is associated with excellent outcomes, complications, such as pump thrombosis continue to affect patients on hemodynamic support. We report the history of a 68-year-old man who underwent implantation of an HeartMate 3 TM as a bridge to transplantation. Nineteen months later, he developed signs of heart failure leading to cardiogenic shock. Neither clinical examination nor parameters from the device allowed a clear-cut diagnosis. Only surgical exploration revealed the presence of clots between the polyethylene terephthalate (Dacron®) and polytetrafluoroethylene tubes. This constitutes a weakness of this device for which we propose to the manufacturer for minimal modifications to overcome the problem.